Peran Celebrity Endorser Dan Hedonic Shopping Motivation Terhadap Impulsive Buying Pada Individu Dewasa Awal - Permata Sari, Ni Putu Indah; Indrawati, Komang Rahayu (Jurnal Ilmiah Wahana Pendidikan, 2024)
Humans does shopping to fulfil their needs, but now also a way to reveal one's status. This proves the existence of emotional motives such as impulsive buying. Impulsive buying is spontaneous shopping . Impulsive buying occurs due to internal factors and external factors. External factors are caused by reference groups, such as celebrity endorsers, namely people who promote certain products. Internal factors are caused by materialistic impulses or hedonic shopping motivation. This study aims to look at the role of celebrity endorsers and hedonic shopping motivation on impulsive buying in early adulthood individuals. The sample of this study were men and women aged 18-25 years who had heard of or knew celebrity endorsers. The research used incidental sampling technique with 161 respondents. The measurement tools used are the impulsive buying scale, the celebrity endorser scale, and the hedonic shopping motivation scale. The results of multiple linear regression analysis, the regression coefficient is 0.591, the coefficient of determination is 0.349 with a significance of 0.000 (p <0.05) proving that there is a positive role of celebrity endorser and hedonic shopping motivation on impulsive buying in early adult individuals. This research has implications for consumers and sellers. Consumers can pay attention to goals before shopping so that they can avoid impulsive buying behavior and sellers can provide an overview of the latest consumer shopping behavior so that they are able to set marketing strategies.